USULAN MODEL PENJADWALAN DAN RUTE KUNJUNGAN MENGGUNAKAN METODE HEURISTIK DENGAN MEMPERTIMBANGKAN ONGKOS TRANSPORTASI PADA DISTRIBUTOR BANDUNG 1 PRODUK MINUMAN KEMASAN PT.X - S.Rosalinda
PT X Bandung 1 drinking products merely has some problems related to the scheduling and visiting routes to their retailer service. So far the existing means have no clear and obvious procedures and steps. Several problems eventually arise, that would be; (1) there had been visiting manners to the retailers meanwhile retailers did not require such manners, otherwise (2) the delay of the product demands to the retailer is simply because there is no product replenishment to the retailer. (3) The existing routes cannot fulfill the distance range. These three give significant influence to the increasing transportation cost of PT X Bandung 1. Appropriate scheduling and visiting routes hopefully could result minimum total transportation cost. The main point of this thesis is Periodic Vehicle Routing Problem (PVRP) that is simply a part of Vehicle Routing Problem (VRP). Suggested model developed in this thesis is subjected to the previous model of Chao, et al (1995). Performance criterion that is used would be total transportation cost in 1 period. The fixed decision variables are visiting day, number of supplied products, types of vehicles, and route followed by the retailer in 1 period. The determination of visiting day and number of products supply is done by randomly generating total demands in 1 period and daily vehicle capacity with the condition of the limited visiting manners. The determination of visiting routs is done by parallel-version Clark-wright algorithm as construction method and also 2-opt algorithm as improvement method from construction method. Eventually, overall decision variables are determined heuristically with resulting display. Such resulting display is merely a display of 30th scenario. The result of this thesis showed 18.33% declining total transportation cost for actual system correspond to the actual system and 18.98% correspond to the improvement method. Meanwhile, the declining total transportation cost of construction method is 0.79% corresponds to the improvement method.